Ascent After Decline : Challenges of Growth - Canuto, Otaviano (World Bank, Washington, DC, 2012)
This note examines one of the most fundamental questions to emerge from the Great Recession of 2007-9: how to regrow global economic growth going forward? Although all are painfully aware that it may be 2013 or 2014 before the global economy returns to normalcy, no one is sanguine about medium- to long-term growth prospects. For this reason, the challenging task of 'regrowing growth' will take center stage for politicians and policy makers alike. One point is clear: without a resurrection of strong economic growth in major economies, the likelihood of rapid economic development in poor developing countries is diminished. How various elements will affect growth prospects is less clear, but vitally important. In the terminology of Hausmann and Rodrik (2003), this is a process of discovery and we are in somewhat uncharted territory.